Appropriating technology for accountability: messages from Making All Voices Count - and McGee, Rosemary; Edwards, Duncan; Hudson, Hannah; Anderson, Colin; Feruglio, Francesca (IDS, 2018)
Making All Voices Count was a programme designed to solve the ‘grand challenge’ of creating more effective democratic governance and accountability around the world. It used funding from four donors to support the development and spread of innovative ideas for solving governance problems – many of them involving tools and platforms based on mobile phone and web technologies. Between 2013 and 2017, the programme made grants for innovation and scaling projects that aimed to amplify the voices of citizens and enable governments to listen and respond. It also conducted research and issued research grants to explore the roles that technology can play in securing responsive, accountable government and building an evidence base. This synthesis report reviews the Making All Voices Count’s four-and-a-half years of operational experience and learning. It shares 14 key messages on the roles technologies can play in enabling citizen voice and accountable and responsive governance. These messages are presented in four sections: (1) Applying technologies as technical fixes to solve service delivery problems; (2) Applying technologies to broader, systemic governance challenges ; (3) Applying technologies to build the foundations of democratic and accountable governance systems; (4) Applying technologies for the public ‘bad’, when tech can be dangerous for democracy. The tech optimism of the era in which the programme was conceived can now be reappraised from the better-informed vantage point of hindsight. Making All Voices Count’s wealth of diverse and grounded experience and documentation provides an evidence base that should enable a more sober and mature position of tech realism as the field of tech for accountable governance continues to evolve.